THE INFLUENCE OF RELIGIOUS BELIEFS ON HALAL PURCHASE INTENTION IN NON-MUSLIM CUSTOMERS - Northa Idaman; Muhammad Iqbal Fasa; Siska Lusia Putri (Journal of Halal Research, Policy, and Industry, 2024)
This study investigates the influence of religious beliefs, perceived benefits of halal products, social influence, and attitudes towards halal products on the halal purchase intention among non-Muslim customers in Surabaya. Utilizing a quantitative research design, data were collected from 150 non-Muslim respondents through an online survey distributed via social media. The analysis was conducted using SmartPLS to evaluate the relationships between the constructs. The findings reveal that even among non-Muslim customers, strong religious beliefs can foster positive attitudes towards halal products due to shared ethical and health values. Perceived benefits, including health, ethical, and quality advantages, significantly enhance attitudes towards halal products. Social influence from family, friends, and social media positively impacts non-Muslim customers' attitudes, highlighting the role of social endorsement in shaping perceptions. Furthermore, a positive attitude towards halal products is a strong predictor of purchase intention, indicating that favorable perceptions directly translate into a higher likelihood of purchase. These findings contribute to the understanding of consumer behavior in the context of halal products and offer practical implications for businesses aiming to target non-Muslim customers. By recognizing the importance of religious beliefs, perceived benefits, and social influence, companies can develop more effective marketing strategies to promote halal products beyond the Muslim community. .